Liver-specific transgenic expression of human NTCP in rhesus macaques confers HBV susceptibility on primary hepatocytes - Lauren N. Rust; Jochen M. Wettengel; Sreya Biswas; Junghyun Ryu; Nadine Piekarski; Sofiya Yusova; Savannah S. Lutz; Spandana Naldiga; Brayden J. Hinrichs; Michelle N. Sullivan; Jamie O. Lo; Ulrike Protzer; et al. (Proceedings of the National Academy of Sciences, 2025)
Hepatitis B virus (HBV) poses a significant global health challenge, necessitating the urgent development of curative therapeutics. However, this progress is impeded by the lack of robust, immunocompetent preclinical animal models due to HBV’s strict species specificity. We previously showed that vector-mediated expression of the HBV entry receptor, human sodium-taurocholate cotransporting polypeptide (hNTCP), renders macaques fully susceptible to HBV infection. In this study, we have generated transgenic macaques expressing hNTCP, marking the creation of the first transgenic nonhuman primate model for infectious disease research. We used PiggyBac (PB) transposon technology to insert a liver-specific hNTCP expression cassette into rhesus macaque zygotes and transferred the resulting embryos into surrogate females, resulting in two healthy transgenic offspring. In both animals, hNTCP is highly and selectively expressed in the liver. Most importantly, we show that isolated hepatocytes from these monkeys are susceptible to HBV infection. These findings lay the foundation for the development of a nonhuman primate HBV model, facilitating the advancement and validation of curative HBV therapies.